Level of professionalism among teachers public elementary schools district of Cainta I and II, Division of Rizal - Nonsol, Gerardo C. (Manila : National University, 2006)
Interaction requires thinking for message to be carefully thought of and understood before communication can be successful. Considering the tremendous potential of the human mind as an avenue for developing correct values, it behooves every teacher to provide the environment and activities to develop students thinking ability. In this context, the teacher is not one who simply provides information, facts or knowledge. He gives freedom to the students to learn by providing the stimuli for the exercise of the learners thinking powers, so they will be able to grapple with the crucial issues and challenges confronting them everyday.
Title page -- Approval Sheet -- Acknowledgement -- Dedication -- Abstract -- Chapter 1. The Problem and its setting -- Chapter 2. Review of related literature and studies -- Chapter 3. Research Design and Methodology -- Chapter 4. Presentation, analysis, and interpretation of data -- Chapter 5. Summary, Conclusion, and recommendation -- Bibliography -- Appendices -- Curriculum Vitae.
Research Method : Descriptive Method.
Includes bibliographical references.